2006
DOI: 10.1086/508164
|View full text |Cite
|
Sign up to set email alerts
|

The 10 μm Infrared Band of Silicate Dust: A Laboratory Study Comparing the Aerosol and KBr Pellet Techniques

Abstract: The profile of the silicate 10 mm IR band contains important information about the evolutional stage of dust in circumstellar environments and the possible ongoing process of planetesimal formation. In order to extract this information, the observed band profiles are compared with calculated or laboratory-measured absorption cross sections of amorphous and crystalline grains with different sizes and compositions. We present in this study the first laboratory measurements of the 10 mm band profiles of nonembedd… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
76
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 52 publications
(84 citation statements)
references
References 15 publications
8
76
0
Order By: Relevance
“…And yet, many uncertainties remain on the optical properties of these grains. For instance Tamanai et al (2006) showed the differences in band positions and band widths of the emissivity profiles for several species (crystalline forsterite and enstatite or amorphous Mg 2 SiO 4 ) when using two different laboratory techniques (KBr pellets versus aerosol measurements). These measured emissivity profiles are also different from absorption efficiencies calculated using optical constant measurements.…”
Section: The Dust Setupmentioning
confidence: 99%
See 3 more Smart Citations
“…And yet, many uncertainties remain on the optical properties of these grains. For instance Tamanai et al (2006) showed the differences in band positions and band widths of the emissivity profiles for several species (crystalline forsterite and enstatite or amorphous Mg 2 SiO 4 ) when using two different laboratory techniques (KBr pellets versus aerosol measurements). These measured emissivity profiles are also different from absorption efficiencies calculated using optical constant measurements.…”
Section: The Dust Setupmentioning
confidence: 99%
“…As mentioned previously, these efficiencies suffer from uncertainties at different levels. Laboratory measurements are unfortunately subject to various environmental effects such as electromagnetic polarization of the embedding medium (KBr, CsI or PE) when using the pellet technique (see Tamanai et al 2006Tamanai et al , 2009. Additionally, when using the optical constant, scattering theories have their own caveats, as discussed for example in Min et al (2007) for the Mie and DHS theories.…”
Section: Forsterite and Crystalline Olivine Grainsmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, measurements of infrared absorption spectra in the laboratory also have been carried out in the regime of Rayleigh scattering. The work of Tamanai et al (2006) is an experimental study of the dependency of the extrinsic properties of IR spectra. Using aerosol techniques, particles were well dispersed in air, and the structures of the particles can be analyzed by in situ microscopic imaging.…”
Section: Introductionmentioning
confidence: 99%